Fe3O4 Nanoparticles Embedded Sodium Alginate/PVP/Calcium Gel Composite for Removal of Cd2+. (4th June 2015) - Jiao, Long; Qi, Peishi; Liu, Yunzhi; Wang, Bo; Shan, Lili
Abstract : Magnetic ferroferric oxide (Fe3 O4 ) nanoparticles embedded sodium alginate (SA)/polyvinylpyrrolidone (PVP)/calciumgel composites (MSPC) were synthesized for the removal of Cd 2+ . The physicochemical properties of the composite gel ball were characterized by scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), power X-ray diffraction patterns (XRD), and vibrating sample magnetometer (VSM). Quantitative adsorptions experiments were performed in view of sorbent dosage, pH, contact time, and temperature. Results showed that the optimum quantity of particles was 1.2 g· L −1, when the Cd 2+ concentration was fixed at 150 mg/L. The optimum pH for adsorption is 6.2. When the initial Cd 2+ concentration was from 50 to 200 mg· L −1, the adsorption equilibrium time was 80–120 minutes. The isotherms results showed the maximum sorption was 97.8 mg/g calculated from the Langmuir isotherm. The pseudo-second-order kinetic model could be well described by the sorption of Cd 2+ in the sediment. The correlation coefficients ( R 2 ) were all higher than 0.96. Results showed that MSPC was a practical and low-cost material for heavy metal removal from the river sediment and simultaneously solves the problems in convenient separation under additional magnetic field.